Effect of metal oxide/alumina on catalytic deoxygentation of biofuel from physic nut residues pyrolysis. (3rd August 2017) - Kaewpengkrow, Prangtip; Atong, Duangduen; Sricharoenchaikul, Viboon
Abstract: Rapid catalytic thermal conversion of Physic nut (Jatropha curcas) residues for upgrading the released vapors was performed using analytical pyrolyzer-gas chromatography/mass spectrometry at 873 K. Conditioning of the evolved vapor product is required since the main vapor products formed without catalysts typically contained around 60% fatty acids, while the total hydrocarbon yields were only 12%. Catalysts tested were alumina (Al2 O3 ) alone and modified by 5 wt% impregnation with various transition metal salts and then calcined to metal oxides. A significant decrease in the proportion of oxygenated compounds (including acids) from 73% without a catalyst to less than 10% with, and an increased conversion to hydrocarbons of more than 70% was obtained with the metal/Al2 O3 catalysts at a Jatropha:catalyst (J:C) ratio of 1:10. The product selectivity was greatly increased as the J:C ratio was increased from 1:1 to 1:10. The total hydrocarbon selectivity of the metal/Al2 O3 catalysts was increased in the order of Pd > Ni > Ce > Ru > La > none > Co > Mo, with the highest proportion of total hydrocarbons obtained being 75%. In addition, only a low yield (<2%) of polycyclic aromatic hydrocarbons was obtained from the conversion of Jatropha curcas residues. However, these catalysts adversely promoted N-containing compounds, suggesting that a further denitrogenation process is necessary. Nevertheless, the overall performance of these transition metal/Al2 O3 catalysts is acceptable and they can be considered as good candidates for bio-oil upgrading. Highlights: Metal/Al2 O3 catalytic upgrading of pyrolytic vapor from Jatropha residues. Synthesized Pd/Al2 O3 as a superior catalyst for deoxygenation. Favorable hydrocarbons selectivity in order of Pd > Ni > Ce > Ru > La > support > Co > Mo. Up to 50% aliphatic hydrocarbons (C5 –C11 ), suitable for gasoline substitution. Low undesired PAHs from upgraded biofuel with synthesized catalysts.